PUBLIC RELATIONS STRATEGY OF EAST JAVA PROVINCE IN MANAGING INSTAGRAM SOCIAL MEDIA @HUMASPROVJATIM - Hisyam, Muhammad (Proceeding of International Conference on Multidisciplinary Research, 2024)
The purpose of this research is to understand the public relations strategy of East Java Province in managing the Instagram social media account @HUMASPROVJATIM and the community's response to its activities. The method used in this study employs a qualitative approach through interviews with targeted informants. The focus of this research is on the public relations of East Java Province. The results show that the implementation of the public relations strategy in East Java Province is quite good, with effective planning during brainstorming sessions. However, there is no specific time or schedule for posting content. Nevertheless, the quality and packaging of the content are varied and engaging, which encourages the community to seek information through Instagram @humasprovjatim. The conclusion of the research indicates that the role of public relations in East Java Province in managing social media content on Instagram is satisfactory. To be even more efficient, actions that can be taken include establishing target audiences, creating a timetable for content creation and posting, and distributing it on Instagram.